2016
DOI: 10.3122/jabfm.2016.06.160176
|View full text |Cite
|
Sign up to set email alerts
|

Physician Cost Consciousness and Use of Low-Value Clinical Services

Abstract: Purpose: Choosing Wisely TM engaged medical specialties, creating "top 5 lists" of low-value services. We describe primary care physicians' (PCPs') self-reported use of these services and perceived barriers to guideline adherence. We quantify physician cost consciousness and determine associations with use.Methods: PCP attendees of a continuing medical education conference completed a survey. For each Family Medicine Choosing Wisely behavior, participants reported clinical adherence. Likert scale items assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
(18 reference statements)
0
16
1
Order By: Relevance
“…[46,51]). Two studies identified determinants that were linked to lower use of LVC: professionals' cost-consciousness [42] and perceived usefulness of guidelines as well as self-efficacy with regard to discussing LVC and costs [52].…”
Section: Professional Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…[46,51]). Two studies identified determinants that were linked to lower use of LVC: professionals' cost-consciousness [42] and perceived usefulness of guidelines as well as self-efficacy with regard to discussing LVC and costs [52].…”
Section: Professional Determinantsmentioning
confidence: 99%
“…Evidence included conflicting guidelines [50,59] and inappropriate or inapplicable guidelines for the patient group [52,77], which led to more LVC. Furthermore, professionals' belief that the LVC was, in fact, effective, despite guidelines recommending against its use was reported as a reason for using LVC (e.g.…”
Section: Evidence and Lvc Practice Determinantsmentioning
confidence: 99%
“…7 Repeated BMD testing is commonly performed, with a substantial proportion of women receiving repeated tests within 2 years, a practice questioned by the Choosing Wisely campaign, 8 speaking to the need for guidance to help clinicians make higher-value decisions regarding repeated BMD measurement. [8][9][10] Studies examining BMD loss and transition to osteoporosis have provided insights into BMD testing intervals according to the level of baseline BMD. 11 Subsequent analyses have evaluated time to reach clinically relevant fracture risk for those who fall below the treatment threshold at baseline 12 and the doubling time in fracture risk, 13 although these have not adequately considered baseline fracture risk relative to the treatment threshold, which would be expected to affect treatment eligibility.…”
Section: Introductionmentioning
confidence: 99%
“…Besides dealing with private gain, personal advantages and other potential conflicts of interests, their responsibilities include the wisely use of health care resources, as well as the duty to guarantee the patients’ best interests [2, 3]. In a situation of pressure from patients to order more tests, it is also difficult for the physician to maintain the right cost-conscious behavior [46]. To maintain the base of medicine’s social contract, in times of conflict of interests, physicians need continuous education, exercising the principles of professionalism, enhancing their personal commitment to patients’ welfare and collectivity.…”
Section: Introductionmentioning
confidence: 99%